2014
DOI: 10.1186/1471-2334-14-203
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing adherence in Hepatitis-C infected patients: a systematic review

Abstract: BackgroundAdherence is a crucial point for the successful treatment of a hepatitis-C virus infection. Studies have shown that especially adherence to ribavirin is important.The objective of this systematic review was to identify factors that influence adherence in hepatitis-C infected patients taking regimes that containing ribavirin.MethodsA systematic literature search was performed in Medline and Embase in March 2014 without limits for publication date. Titles and abstracts and in case of relevance, full-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 36 publications
2
44
0
2
Order By: Relevance
“…In both questionnaires week 12 was critical, during which we observed the lowest levels of HRQoL. Similarly, other studies showed lower levels of HRQoL at week 12 of treatment with double therapy (24,28) .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In both questionnaires week 12 was critical, during which we observed the lowest levels of HRQoL. Similarly, other studies showed lower levels of HRQoL at week 12 of treatment with double therapy (24,28) .…”
Section: Discussionsupporting
confidence: 82%
“…However, this treatment is associated with a number of adverse effects such as fatigue, influenza-like symptoms (flu-like), anemia, and neuropsychiatric disorders that affect quality of life and eventually lead to discontinuation of therapy. A study of 1860 patients with chronic hepatitis C treated with PEG-IFN and ribavirin showed a reduction in quality of life scores from SF-36 (24) . Studies evaluating the quality of life in patients undergoing double therapy are scarce and triple therapy even scarcer.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review on RCTs, 66% of patients remained in the trials for at least 80% of duration and received at least 80% of prescribed medicines . In another systematic review, the adherence to treatment among patients who received treatment at tertiary centres was reported from 38% (taking at least 80% of Peg‐IFN plus RBV) to 89% (taking at least 80% of RBV) . Adherence to treatment is a strong predictor for SVR.…”
Section: Discussionmentioning
confidence: 99%
“…Side effects have also been shown to be a predictor of nonadherence [68]. With the next generation DAAs, the severity of side effects have been lessened.…”
Section: Adherence Pharmacology and Complexity Considerations In Hiv/hcmentioning
confidence: 99%